2023
DOI: 10.3390/aerospace10030277
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Powered Aviation—Design of a Hybrid-Electric Regional Aircraft for Entry into Service in 2040

Abstract: Over the past few years, the rapid growth of air traffic and the associated increase in emissions have created a need for sustainable aviation. Motivated by these challenges, this paper explores how a 50-passenger regional aircraft can be hybridized to fly with the lowest possible emissions in 2040. In particular, the use of liquid hydrogen in this aircraft is an innovative power source that promises to reduce CO2 and NOx emissions to zero. Combined with a fuel-cell system, the energy obtained from the liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Intensive research, involving substantial investments, has also started regarding commuter aircraft or regional transport planes. In [23], the study explores how a regional aircraft with 50 passengers can be hybridized to achieve the lowest possible emissions by 2040.…”
Section: Electric Aircraft With Fuel Cells Already Developed and Unde...mentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive research, involving substantial investments, has also started regarding commuter aircraft or regional transport planes. In [23], the study explores how a regional aircraft with 50 passengers can be hybridized to achieve the lowest possible emissions by 2040.…”
Section: Electric Aircraft With Fuel Cells Already Developed and Unde...mentioning
confidence: 99%
“…The FUTPRINT50 project, funded by the EU, focuses on possible technologies for hybridelectric commercial aircraft for the years 2035-2040 [25]. In [23], the authors have designed the hybrid regional aircraft HAIQU (Hydrogen Aircraft designed for Quick commuting). This aircraft offers a capacity of 50 passengers and features a hybrid power system based on fuel cell and battery technology, combining the advantages of both technologies.…”
Section: Electric Aircraft With Fuel Cells Already Developed and Unde...mentioning
confidence: 99%
“…where µ is the permeability, σ is the conductivity, and the boundary condition of the magnetic vector potential is set as A = 0. Referring to the cooling systems in previous studies, we designed a modular pipe cooling system as shown in Figure 8 [40,41]. In the cooling system, each HTS coil was contained in a modular pipe separately and cooled by liquid hydrogen.…”
Section: Cooling System Design and Ac Lossmentioning
confidence: 99%
“…Despite the challenges in bringing the HEPS into service, as reviewed by different researchers [7][8][9], a significant reduction in fuel energy consumption [10] makes the technology promising for green aviation. It is also anticipated that the advantages of the HEPS will be further enhanced by applying hydrogen fuel and fuel cell technology [11]. The architectures of the HEPS include series, parallel, and turbo-electric configurations.…”
Section: Introductionmentioning
confidence: 99%